Comparison of Sentinel and Bactec blood culture systems. Issue 9 (September 1992) - Stevens, M; Patel, H; Walters, A; Burch, K; Jay, A; Dowling, N; Mitchell, C J; Swann, R A; Willis, A T; Shanson, D C
Abstract : AIMS: To evaluate the Sentinel automated blood culture system and to compare its performance with that of Bactec. METHODS: The Sentinel blood culture system was evaluated in three centres. The performance of the system was assessed in comparison with the routine blood culture method used in these centres, the Bactec system. RESULTS: Blood culture sets (n = 2180) consisting of Sentinel aerobic and anaerobic, and Bactec aerobic and anaerobic bottles yielded 218 (10%) clinically important isolates. One hundred and fifty five (71%) of the isolates were detected by both systems; 35 (16%) were detected by Sentinel only; and 28 (13%) by Bactec only. For the duration of the evaluation, the Sentinel system was deliberately configured so that it was impossible to detect positive results during the first 12 hours. The times to positivity after the first 12 hours were similar. Data gathered during and subsequent to the evaluation have been used by the manufacturer to refine the algorithm so that positive results can be detected at a minimum of 2.25 hours. CONCLUSIONS: After a period of familiarization the Sentinel system was considered easy to use. Sentinel is a useful addition to the methods available for the detection of bacteria in blood cultures.